Percutaneous nephrostomy or double J stenting, which is better modality for obstructive uropathy-a descriptive study - Mittal, Vinamra; Biswas, Manoj; Lal, Shobha (International Journal of Research in Medical Sciences, 2017)
Background: Percutaneous Nephrostomy or Ureteric Stenting is indicated in patients with Acute Renal Failure following urinary tract obstruction. The purpose of this study was to evaluate the better treatment modality in terms of S. Creatinine level. Methods: Total 50 patients with Creatinine level of >2 mg/dl and hydronephrosis due to upper urinary tract obstruction were grouped into either percutaneous nephrostomy or stent insertion groups. These patients were then evaluated by overall trend of S. creatinine and urine output levels postoperatively. Results: Two comparable groups of PCN and DJS were formed with a mean age of 45.5 years and 47.9 years. Male to female ratio was 1.5:1 and 1.2:1 respectively. Pain with oliguria or anuria was the major presentation. The urine output levels showed a sudden increase postoperatively with a subsequent trend towards normal value in both the groups. Creatinine however showed a normalizing trend from a mean 6.46 mg/dl preoperatively to 1.01mg/dl postoperatively in PCN group whereas in DJS group 5.38mg/dl preoperatively to 2.75mg/dl with a rising trend from POD 15 requiring conversion to PCN in 20% of patients with subsequent normalization of creatinine levels to 0.95 mg/dl. Statistically we found no difference in the outcome when both the groups were compared in view of serum creatinine and urine output levels whereas there is a significant difference in the pre and post operative outcome of both the groups. Conclusions: Our results thus support that though there is no significant difference among both the procedures, ureteral stents are associated with intolerable lower urinary tract symptoms owing to conversion to secondary percutaneous Nephrostomy. Hence percutaneous nephrostomy is superior to ureteral stents for diversion of urine in patients with ARF due to obstructive uropathy.